Green leadership and competitive advantage: The role of mediation from knowledge management and talent management - Tri Juniarti, Atty; Indra Setia, Bayu; Alghifari, Erik Syawal; Sya’roni, Deden Abdul Wahab (Journal of Eastern European and Central Asian Research (JEECAR), 2024)
This research aims to analyze the impact of green leadership on competitive advantage through the mediating roles of knowledge management and talent management. In the context of the Industrial Revolution 4.0 (IR4.0), where technology companies worldwide have international ramifications on innovation, sustainability issues, and environmental impacts such as carbon emissions, e-waste, and natural resource extraction that garner global attention, we chose technology companies in Indonesia as a model. Data was collected using an e-questionnaire, distributed to company managers, and then analyzed using SEM-AMOS. The research results demonstrate that green leadership does not have a direct influence on competitive advantage but rather exerts an indirect influence through knowledge management and talent management. These findings strengthen the view that sustainable strategy must be an essential part of an organization’s efforts to achieve competitive advantage.